Structural and Quantitative Analysis of Three C-Glycosylflavones by Variable Temperature Proton Quantitative Nuclear Magnetic Resonance - Jing Liu; Yang Liu; Zhong Dai; Lan He; Shuangcheng Ma (Journal of Analytical Methods in Chemistry)
Quantitative nuclear magnetic resonance is a powerful tool in drug analysis because of its speed, precision, and efficiency. In present study, the application of variable temperature proton quantitative nuclear magnetic resonance (VT-1H-qNMR) for the calibration of three C-glycosylflavones including orientin, isoorientin, and schaftoside as reference substances was reported. Since there was conformational equilibrium due to the restricted rotation around the C(sp3)-C(sp2) bond in C-glycosylflavones, the conformational behaviors were investigated by VT-NMR and verified by molecular mechanics (MM) calculation. The VT-1H-qNMR method was validated including the linearity, limit of quantification, precision, and stability. The results were consistent with those obtained from mass balance approach. VT-1H-qNMR can be deployed as an effective tool in analyzing C-glycosylflavones.